Novel ABCB1 and ABCC Transporters Are Involved in the Detoxification of Benzo(α)pyrene in Thick Shell Mussel, Mytilus coruscus - Guo, Baoying; Xu, Zhongtian; Yan, Xiaojun; Buttino, Isabella; Li, Jiji; Zhou, Chao; Qi, Pengzhi (Frontiers in Marine Science, 2020)
ATP-binding cassette (ABC) transporters play an essential role in xenobiotic resistance through transporting xenobiotics into or out of cells. However, their functional role in mollusk's defense against polycyclic aromatic hydrocarbons (PAHs) remains unclear. In the present study, novel McoABCB1 and McoABCC transporters were identified in the gills of Mytilus coruscus, and their benzo(α)pyrene (Bap) detoxification function was determined by qRT-PCR and efflux assays. McoABCB1 and McoABCC genes were constitutively expressed in all tissue types, suggesting the primary physiological function of these transporters. Bap, a chemical stress agent, could induce the mRNA expression of McoABCB1 and McoABCC in gills. However, at high concentration, Bap inhibited their expression levels at the late stage. Besides, the efflux activities in M. coruscus gills showed a dose-dependent elevation in a Bap pre-exposure group, compared with those in a reversin 205 or MK571 treatment alone group. These results demonstrated the presence of ABCB1 and ABCC transporters in Mytilus coruscus, and their involvement in cellular Bap detoxification.